2012
DOI: 10.1026/0012-1924/a000059
|View full text |Cite
|
Sign up to set email alerts
|

Wer riskiert eine Mahnung?

Abstract: Inwieweit kann Gewissenhaftigkeit nach dem NEO-PI-R auf Faktor- und Facettenebene zur Diagnostik der dispositionellen Selbstregulation herangezogen werden? Wir haben dies exemplarisch anhand einer Handlung mit hohen Selbstregulationserfordernissen untersucht: dem Ausleihen, fristgerechten Durcharbeiten und pünktlichen Zurückgeben von Bibliotheksbüchern. Defizite in der Handlungsregulation wurden dabei als Verhaltensspur über Einträge in der Bibliotheksdatenbank erhoben. Über die NEO-PI-R-Skala Gewissenhaftigke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Furthermore, Carranza Esteban et al (2023) found that academic self-e cacy and procrastination can predict research motivation. Quispilaya-Capcha (2023) underscores the negative impact of procrastination on selfe cacy, while Oram and Rogers (2022) stress the importance of satisfying basic psychological needs to increase academic motivation and reduce procrastination Kröner and Fritzsche (2012). suggest that selfdiscipline is the most crucial facet of conscientiousness when explaining procrastination.…”
mentioning
confidence: 99%
“…Furthermore, Carranza Esteban et al (2023) found that academic self-e cacy and procrastination can predict research motivation. Quispilaya-Capcha (2023) underscores the negative impact of procrastination on selfe cacy, while Oram and Rogers (2022) stress the importance of satisfying basic psychological needs to increase academic motivation and reduce procrastination Kröner and Fritzsche (2012). suggest that selfdiscipline is the most crucial facet of conscientiousness when explaining procrastination.…”
mentioning
confidence: 99%